The link between body size, colouration and thermoregulation and their integration into ecogeographical rules: a critical appraisal in light of climate change. Issue 6 (11th February 2022) - Goldenberg, Jonathan; Bisschop, Karen; D'Alba, Liliana; Shawkey, Matthew D.
Abstract : Biological rules describe general morphological, structural and genetic patterns within and across species. Within these, ecogeographical rules correlate phenotypic variation of organisms with biogeography. The latter have been developed over the last 150 years, and recently have gained renewed attention due to climate change, as researchers try to predict how species will respond to different environmental conditions based on certain phenotypic features. However, there is no agreement whether such rules hold true in our rapidly changing world. Among the ecogeographical rules, six have focused on the contributions of the coloured integument and body size to the thermal balance of individuals. They are therefore particularly relevant for predicting how species' phenotypes will respond to future climatic scenarios. Here, we provide an overview and discuss these ecogeographical rules, particularly in light of thermoregulation, and probe the extent to which these rules apply, and the taxonomic levels at which they are relevant. The predictions of these rules often contradict each other, and indeed we argue that use of the word 'rule' itself hinders their careful investigation. Moreover, disrupted climate patterns and global warming alter the environmental conditions under which these rules were once formulated. Thus, these rules may be outdated in our current rapidly changing environment. We conclude by proposing a revised concept of ecogeographical rules, where the micro‐environment should have a stronger influence on the phenotype of organisms than its geographical location, and we suggest precautions researchers should take when testing them.